ChemInform Abstract: Saccharothriolides A—C, Novel Phenyl‐Substituted 10‐Membered Macrolides Isolated from a Rare Actinomycete Saccharothrix sp. Issue 37 (September 2015) - Lu, Shan; Nishimura, Shinichi; Hirai, Go; Ito, Masashi; Kawahara, Teppei; Izumikawa, Miho; Sodeoka, Mikiko; Shin‐ya, Kazuo; Tsuchida, Toshio; Kakeya, Hideaki
Abstract Saccharothriolide B (Ib) demonstrates moderate cytotoxicity against cancer cell lines HeLa and HT1080.